POCKET MONEY AND SELF-CONTROL OF STUDENTS' CONSUMPTION PATTERNS - Agustyanto, Muhammad Roofid; Ranita, Sylvia Vianty (Proceeding International Seminar of Islamic Studies, 2024)
Everyone consumes, including students. Students are the easiest subject to follow changes in the flow of globalization which is synonymous with modern things. Change makes students progress further. Human change towards a more advanced direction is called modernization. Many students follow fashion trends, shop online, follow gadget developments and even vacation in famous places. Apart from that, the many shopping centers also increase the attraction for students to visit them. This research aims to analyze the perceptions and factors that influence the consumption patterns of FEB UMSU students which are able to increase or control students' consumptive values. The sampling technique used a non-probability sampling method and a sample of 93 respondents was obtained. The type of data used is primary data sourced from the results of distributing questionnaires. This research uses the Structure Equation Model (SEM) analysis method using the SmartPLS data processing tool. The research results show that the pocket money factor has a significant influence on students' consumption patterns and self-control has a significant influence on the consumption patterns of students at the Faculty of Economics and Business, Muhammadiyah University, North Sumatra.